Graduate employability and graduate (Un)employment in Sabah: issues, challenges and prospects for Universiti Malaysia Sabah - Lai, Yew Meng (Solid State Technology, 2020)
This article dwells on the critical agenda of Graduate Employability and Graduate (Un)Employment in Sabah, generally, and Universiti Malaysia Sabah (UMS), specifically. It begins by highlighting the definitional problematique of “Graduate Employability” versus “Graduate Employment”, and how the blurring of their subtle distinctions have brought salient implications on the traditional roles and responsibilities of universities. The article proceeds by discussing in detail the issues and challenges faced by UMS when it comes to addressing the phenomenon of graduate unemployment, which are caused by both structural and agential determinants. This is followed by a comprehensive description of the plethora of policies, strategies and action plans proposed and employed by the varsity as well as the Sabah state government in seeking to address, while simultaneously transform the existing Graduate Employability (GE) challenges into opportunities. Anchored on the “Triple Helix” concept, it is hoped that these efforts undertaken by UMS together with the state and the industries would be effective in enhancing its annual GE performance, and most importantly in realising the overriding goal of transforming the varsity’s students into future-proof graduates.